2011
DOI: 10.1524/zkri.2011.1337
|View full text |Cite
|
Sign up to set email alerts
|

Electron crystallography of MWW zeolites – filling the missing cone

Abstract: Given that many zeolites crystallize in habits that lead to preferred orientation, and that there is a AE60 tilt limitation in many electron microscope goniometer stages, collection of a three 3-D electron diffraction data set from these materials is severely restricted. To overcome this, preparative measures must be taken to produce other sample orientations. Using a number of MWW framework zeolites (MCM-22, MCM-22P, MCM-49, ITQ-1) as examples, thin-sectioned views onto the edge stacking of lamellar layers ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The appearance of the prepared MCM-22 crystals that can be seen in Figure 2S (TEM image), Supporting Information, shows typical characteristics. 1 They comprise thin plates, oriented almost exclusively flat-on, preventing estimation of their thickness, 45 some showing distinctly hexagonal shape. The widths vary considerably, falling in the approximate range from 50 to 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of the prepared MCM-22 crystals that can be seen in Figure 2S (TEM image), Supporting Information, shows typical characteristics. 1 They comprise thin plates, oriented almost exclusively flat-on, preventing estimation of their thickness, 45 some showing distinctly hexagonal shape. The widths vary considerably, falling in the approximate range from 50 to 500 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned treatments and operations are not only sources of problems but may also lead to an advantage, as reported for MWW crystal that were extruded, jet-milled, and subject to other potentially degrading treatments. It was observed that, in contrast to standard samples showing mainly flat-on crystal orientation, the treated ones contained many edge-on crystals . This apparently more random spatial orientation and maybe some fragmentation may contribute to high performance, for example, as for MCM-56 mentioned in the preceding paragraph.…”
Section: Challenges and Opportunitiesmentioning
confidence: 91%
“…It was observed that, in contrast to standard samples showing mainly flat-on crystal orientation, the treated ones contained many edge-on crystals. 260 This apparently more random spatial orientation and maybe some fragmentation may contribute to high performance, for example, as for MCM-56 mentioned in the preceding paragraph.…”
Section: Challenges and Opportunitiesmentioning
confidence: 97%
“…The main advantage of the mesoporous distribution generated in the MCM-36 was the easy accessibility achieved to internal acid active sites, overall for voluminous reactant molecules which take part in different catalytic processes [106]. On the contrary, the pillared materials, such as the MCM-36 zeolites, show the important inconvenient associated to the partial blockage of active sites, present in the external surface of MWW layers, due to the intercalation of silica pillars in the interlayer space [107].…”
Section: Mcm-36: Pillared Zeolitic Materials With Mww Topologymentioning
confidence: 99%